ANALISIS PENGARUH NILAI TRANSAKSI SAHAM SYARIAH TERHADAP PERGERAKAN IHSG DI BURSA EFEK INDONESIA TAHUN 2023-2025 - Yusrina Arfah Lubis; Cindy Andriani; Febriana Krisdayanti Barus; Putri Kemala Dewi Lubis (JIM : Journal Of International Management, 2026)
This study aims to empirically examine the effect of sharia stock transaction value on the Composite Stock Price Index (IHSG) at the Indonesia Stock Exchange during 2023–2025. Using a quantitative approach with simple linear regression (OLS), secondary time series data from the IDX and OJK were analyzed. The results show that sharia stock transaction value has a positive and statistically significant effect on IHSG. The coefficient of determination (R-Squared) of 0.590602 indicates that approximately 59.06% of IHSG variation is explained by sharia stock transaction value. These findings confirm that increased trading activity in the sharia stock segment provides positive market sentiment and strengthens the sharia capital market as a key driver of IHSG movement in Indonesia.